Trends towards stronger primary care in three western European countries; 2006-2012. Issue 1 (December 2016) - van Loenen, Tessa; van den Berg, Michael; Heinemann, Stephanie; Baker, Richard; Faber, Marjan; Westert, Gert
Abstract Background Strong primary care systems are believed to have an important role in dealing with healthcare challenges. Strengthening primary care systems is therefore a common policy goal for many countries. This study aims to investigate whether the Netherlands, the UK and Germany have strengthened their primary care systems in 2006-2012. Method For this cross-sectional study, data from the International Health Policy surveys of the Commonwealth Fund in 2006, 2009 and 2012 were used. The surveys represent the experiences and perspectives of primary care physicians with their primary care system. The changes over time were researched in three areas: organization of primary care processes, use of IT in primary care and use of benchmarking and financial incentives for performance improvement. Results Regarding organization of primary care processes, in all countries the use of supporting personnel in general practice increased, but at the same time practice accessibility decreased. IT services were most advanced in the UK. The UK and the Netherlands showed increased use of performance feedback information. German GPs were least satisfied with how their system works across the 2006-2012 timeframe. Conclusion All three countries show trends towards stronger primary care systems, although in different areas. Coordination and comprehensive care through the assignment of assisting personnel and use of disease management programs improved in all countries. In the Netherlands and the UK, informational continuity is in part ensured through better IT services. All countries showed increasing difficulties upholding primary care accessibility.